Synthesis, Characterization and Biological Efficacies from Some New Dinuclear Metal Complexes for Base 3-(3,4-Dihydroxy-phenyl)-2-[(2-hydroxy-3-methylperoxy-benzylidene)-amino]-2-methyl Propionic Acid - Shatha Mohammed Hassan Obaid; Jasim Shihab Sultan; Abbas Ali Salih Al-Hamdani (Indonesian Journal of Chemistry, 2020)
The reaction of methyldopa with o-vanillin in refluxing ethanol afforded Schiff base and characterized through physical analysis with a number of spectra also the study of biological activity. The geometry of the Schiff base was identified through using (C.H.N) analysis, Mass, 1H-NMR, FT-IR, UV-Vis spectroscopy. Metal complexes of Cr3+, Mn2+, Co2+, Ni2+, Cu2+, Zn2+, Cd2+ and Hg2+ with Schiff base have been prepared in the molar ratio 2:1 (Metal:L), (L = Schiff base ligand) except Hg2+ at molar ratio 1:1 (Hg:L). The prepared complexes were characterized by using Mass, FT-IR and UV-Vis spectral studies, on other than magnetic properties and flame atomic absorption, conductivity measurements. According to the results a dinuclear octahedral geometry has been suggested for Cr3+, Mn2+, Co2+, Ni2+, Cu2+ and Zn2+ complexes, dinuclear tetrahedral for Cd2+ and mononuclear tetrahedral for Hg2+ complex. This work highlights the relevance of metal complexation strategy to stabilize the ligands and improve their bioactivity. Schiff base complexes have been screen for their antibacterial activity against Gram negative and positive bacteria and antifungal activity showing promising antibacterial and biological activity.